Difficult Asthma: Consider All of the Possibilities. Issue 5 (3rd October 2000) - Cicutto, Lisa C; Chapman, Kenneth R; Chamberlain, Dean; Downey, Gregory P
Abstract : Asthma is a common respiratory disease that can often be managed successfully. However, there are patients that do not respond to the maximum doses of standard therapy and subsequently have a reduced quality of life. Many factors can contribute to a failure to respond to treatment, and a comprehensive approach is important when assessing and evaluating these patients. This report describes a patient referred for 'difficult to control asthma' who had multiple emergency department visits and hospitalizations. In addition to a history of wheezing, spirometry showed impaired flow and vital capacity was reduced. Further investigation showed a normal total lung capacity, and a computed tomography scan revealed main bronchus blockage by a tumour, which was confirmed by bronchoscopy. This led to a surgical resection of a mucoepidermoid carcinoma. This case highlights the need to consider all possibilities during the evaluation of patients with difficult asthma.